Analysis on the operating performance of 5-kW class solid oxide fuel cell-internal combustion engine hybrid system using spark-assisted ignition. (15th February 2020) - Kim, Jaehyun; Kim, Yongtae; Choi, Wonjae; Ahn, Kook Young; Song, Han Ho
Highlights: Stable combustion (COV 5–7%) of anode off-gas is achieved by spark-assisted ignition. There is almost no NOX emission in the engine exhaust ( 3 ppm at 15% O2 level). Exergy efficiency of 37% is achieved in the spark-assisted ignition engine. Thermal self-sustainability of the 5-kW class hybrid system is improved. Efficiency of 61.6% is achieved in the hybrid system using spark-assisted ignition. Abstract: The objective of the proposed hybrid system is to increase the system efficiency by using the residual fuel of the anode off-gas from a solid oxide fuel cell in an internal combustion engine (ICE). In this study, a novel hybrid system using spark-assisted ignition (SAI) in an ICE operation is proposed. Since this is the first attempt of using a new combustion concept in a hybrid system, feasibility of SAI and its effect on the system operation are investigated in this study. To analyze the effect of the combustion on the system, the engine experiments on the SAI were conducted by changing the engine operating parameters, such as the intake temperature, equivalence ratio, and spark timing. For the system-level analysis, a zero-dimensional model for the fuel cell and the balance of plants was developed and validated. The results of the engine experiments were integrated directly with the system model. The performance of the hybrid system using SAI was analyzed from the energy and exergy perspectives. Under the operating conditions of this study, the anode off-gas combustion can be controlled stably (COV: 5–7%) through the SAI, even though the intake temperature is decreased to 280 °C at the low compression ratio of 8.2. It leads to an increase in exergy efficiency of the engine to 37%. Consequently, thermal self-sustainability is improved and the indicated efficiency of 61.6% is achieved in the hybrid system. The SAI engine is responsible for 14% of the system power and produces considerably low NOX emissions (< 3 ppm at 15% O2 on a dry basis).